Identification and Optimization of the Algicidal Activity of a Novel Marine Bacterium Against Akashiwo sanguinea - Li, Shuangfei; Wang, Shilin; Xie, Linshen; Liu, Yan; Chen, Huirong; Feng, Jie; Ouyang, Liao (Frontiers in Marine Science, 2022)
Akashiwo sanguinea is a marine algal species associated with harmful algal blomms. This study is the first to report that Vibrio brasiliensis H115, isolated from the seawater of Dameisha Bay (Shenzhen), China is capable of lysing A. sanguinea. Strain H115 exhibited efficient algicidal activity against A. sanguinea, with algicidal efficiencies of 73.9±1.8% and 81.4±2.8% after 10 min, at bacterial to algal cell ratios of 7000:1 and 8000:1, respectively. The strain attacks A. sanguinea by secreting extracellular active compounds, in an indirect mode. Single-factor and uniform design experiments showed that the optimum growth conditions for strain H115 were: 2216E medium with extra sorbitol (1.0%) and peptone (2.0%), pH 7.5, a shaking speed of 200 rpm, and incubation at 40 ℃ for 54 h. Under these optimized conditions, algicidal efficiency of strain H115 against A. sanguinea improved by 69.4%. Strain H115 showed better performance when the growth volume was increased to 5 L and 100 L bioreactors, with algicidal efficiencies reaching 94.2±0.5% and 97.1±0.6% after 4 h, respectively. These results suggest that strain H115 and its active algicidal compounds has the potential to be used to control the outbreaks of A. sanguinea.